2009
DOI: 10.1037/a0014686
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of individual and couple behavioral alcohol treatment for women.

Abstract: Although alcohol use disorders (AUDs) adversely affect women, research on efficacious treatments for women is limited. In this randomized efficacy trial of 102 heterosexual women with AUDs, the authors compared alcohol behavioral couple therapy (ABCT) and alcohol behavioral individual therapy (ABIT) on percentage of days abstinent (PDA) and percentage of days of heavy drinking (PDH) over 6 months of treatment and 12 months of posttreatment follow-up. Baseline relationship functioning and comorbid disorders wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
198
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(210 citation statements)
references
References 48 publications
8
198
1
3
Order By: Relevance
“…(Fals-Stewart et al 1996, 2006McCrady et al 2009;Winters et al 2002). However, in the three studies that measured client satisfaction with treatment, no differences were found between the groups.…”
Section: Introductionmentioning
confidence: 58%
“…(Fals-Stewart et al 1996, 2006McCrady et al 2009;Winters et al 2002). However, in the three studies that measured client satisfaction with treatment, no differences were found between the groups.…”
Section: Introductionmentioning
confidence: 58%
“…Treatment condition was dummy-coded with IBT as the reference group. Following prior research (McCrady, et al 2009), PDA was arcsine-transformed to improve normality. Baseline days of non-study-based treatment was square root-transformed to improve normality.…”
Section: Methodsmentioning
confidence: 99%
“…In a randomized controlled trial, Peters et al (2011) identified numerous benefits of involving relatives in relapse prevention, including improved understanding of the disorder, increased efficacy in relatives' ability to manage the illness, and improved relationships. Across clinical presentations, there is strong evidence for the benefits of including social supports in the treatment (e.g., Copello et al, 2005;McCrady et al, 2009;McGorry, 2009;Rea et al, 2003;Shimazu et al, 2011). Commonly, benefits include improved treatment retention, improved client recovery, enhanced relationships, and improved family well-being.…”
Section: Bringing Social Supports Into the Treatment Milieumentioning
confidence: 96%
“…In substance use disorder treatment, McCrady et al (2009) showed that couple behavioral therapy for alcohol dependence was more effective than individual behavioral therapy. Further, social interventions, used in combination with individual treatment, have been shown to be more effective than individual treatment alone.…”
Section: Bringing Social Supports Into the Treatment Milieumentioning
confidence: 98%